2020
DOI: 10.1177/1756284819895435
|View full text |Cite
|
Sign up to set email alerts
|

Menadione reduces CDC25B expression and promotes tumor shrinkage in gastric cancer

Abstract: Background: Gastric cancer is one of the most incident types of cancer worldwide and presents high mortality rates and poor prognosis. MYC oncogene overexpression is a key event in gastric carcinogenesis and it is known that its protein positively regulates CDC25B expression which, in turn, plays an essential role in the cell division cycle progression. Menadione is a synthetic form of vitamin K that acts as a specific inhibitor of the CDC25 family of phosphatases. Methods: To better understand the menadione m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…CDC25B dephosphorylates and activates cyclin-dependent kinase/cyclin complex (CDK1/Cyclin B), which is responsible for cell cycle G2-M transition [ 33 36 ]. It has reported that CDC25B inhibitors (vitamin K analogs like adociaquinone B [ 37 ], NSC 663284 [ 38 ], and menadione [ 39 ].) could inhibit CDC25B diphosphatase activity and suppress tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…CDC25B dephosphorylates and activates cyclin-dependent kinase/cyclin complex (CDK1/Cyclin B), which is responsible for cell cycle G2-M transition [ 33 36 ]. It has reported that CDC25B inhibitors (vitamin K analogs like adociaquinone B [ 37 ], NSC 663284 [ 38 ], and menadione [ 39 ].) could inhibit CDC25B diphosphatase activity and suppress tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Menadione has been reported to exhibit anticancer activity in vitro, primarily by generating reactive oxygen species, which lead to DNA damage and cell death (48)(49)(50). Previous studies have demonstrated that in GC, menadione induces cell cycle arrest and apoptosis, and inhibits tumor development and progression in vivo (51)(52)(53). Several clinical trials have evaluated the synergistic cytotoxicity of menadione with other anticancer drugs.…”
Section: A B C Dmentioning
confidence: 99%
“…The cofactor vitamin K 1 (phylloquinone) undergoes intracellular redox chemistry via its reduction (by nicotinamide adenine dinucleotide, NADH) or epoxidation, essential reactions in blood coagulation, and cell proliferation . The derivative vitamin K 3 (menadione) has shown promising tumor-killing properties . Menadione causes intracellular oxidation via the production of ROS disturbing the intracellular redox balance (oxidative stress-induced cytotoxicity). , …”
Section: Introductionmentioning
confidence: 99%
“…The derivative vitamin K 3 (menadione) has shown promising tumor-killing properties . Menadione causes intracellular oxidation via the production of ROS disturbing the intracellular redox balance (oxidative stress-induced cytotoxicity). , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation